2008
DOI: 10.1634/stemcells.2008-0030
|View full text |Cite
|
Sign up to set email alerts
|

IFATS Collection: The Role of Human Adipose-Derived Stromal Cells in Inflammatory Microvascular Remodeling and Evidence of a Perivascular Phenotype

Abstract: A growing body of literature suggests that human adiposederived stromal cells (hASCs) possess developmental plasticity both in vitro and in vivo, and might represent a viable cell source for therapeutic angiogenesis and tissue engineering. We investigate their phenotypic similarity to perivascular cell types, ability to contribute to in vivo microvascular remodeling, and ability to modulate vascular stability. We evaluated hASC surface expression of vascular and stem/ progenitor cell markers in vitro, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
113
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 49 publications
2
113
1
4
Order By: Relevance
“…Some have used the protein Pref1, first identified on murine 3T3-L1 preadipocytes, as a putative ASC marker [24]. Others have reported the use of pericytic markers such as plateletderived growth factor receptor b and 3G5 [23,[25][26][27][28]. Finally, combinatorial phage display approaches have associated the presence of a 5 b 1 integrin with ASCs [29].…”
Section: Product Definitionmentioning
confidence: 99%
“…Some have used the protein Pref1, first identified on murine 3T3-L1 preadipocytes, as a putative ASC marker [24]. Others have reported the use of pericytic markers such as plateletderived growth factor receptor b and 3G5 [23,[25][26][27][28]. Finally, combinatorial phage display approaches have associated the presence of a 5 b 1 integrin with ASCs [29].…”
Section: Product Definitionmentioning
confidence: 99%
“…Furthermore, ASCs, as with MSCs from other tissue sources, secrete numerous growth factors implicated in tissue development and regeneration [18]. As progenitor cells of a perivascular origin (such as in the periosteum) are major contributors to primary bone healing, the putative pericyte origin for ASCs, as well as their association with a perivascular niche [19][20][21][22][23], suggests a role for ASCs as a model for osteoblastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have rejected this notion, and refute that ADSCs can differentiate into ECs/EPCs (Kondo et al, 2009). Several recent studies have indicated that adipose-derived regenerative cells (ADRCs) can differentiate into pericytes in vitro and in vivo (Amos et al, 2008;Traktuev et al, 2008;Zannettino et al, 2008). However, transplantation of ADSCs, as well as SVFs, have demonstrated neoangiogenesis and vasculogenesis in vivo (Guo et al, 2016;Zhong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%